Preparação e caracterização de sistemas superácidos sólidos baseados em sílica-alumina suportada com sulfato metálico - (:unkn) unknown (Universidade Federal do Amazonas, 2017)
Metallic sulfates when used to modify acidic solids have conferred an increase in the acidity of the acidic sites of Lewis and Brønsted, presenting Hammett acidity constant superior to that of sulfuric acid, being called superacid materials. For this reason, superacid materials have been developed and used in many catalytic reactions. In this work the nickel sulfate (NiSO4) and metakaolinite obtained from the kaolinite soil of Manaus - AM were used to synthesize superacid materials varying NiSO4 concentration and calcination temperature. The materials were characterized by chemical analysis (FRX), thermogravimetry (TGA), Infrared Spectroscopy with Fourier Transform (FTIR), X-ray diffraction (XRD), scanning electron microscopy (SEM), adsorption-desorption of N2 (BET method) and still the acidity of the materials was studied by infrared spectroscopy technique of adsorbed pyridine. The catalytic activity was investigated by photodegradation of methylene blue. The characterization results showed that the addition of sulfate ions on the surface of metakaolinite did not alter the structure and morphology of the catalytic support. Bands relative to Lewis acid sites were observed at 1445 and 1607 cm -1 and Brønsted at approximately 1638 cm -1. The metakaolinite sample showed a 43.2% degradation of methylene blue, presenting better performance among all samples tested. Therefore, the characterization of the materials showed that there was interaction between the nickel sulfate and the catalytic support, resulting in the obtaining of the superacid materials and also the addition of nickel sulfate in the catalytic support caused some modification in the surface acidity of metakaolinite. However, the catalytic tests showed that the superacid materials had little catalytic activity for methylene blue photodegradation reactions.
Keywords: Sulfato de níquel; Metacaulinita; Superácido; Fotodegradação; Azul de Metileno; Sulfate; Metakaolinite; Superacid; Photodegradation; Methylene blue; ENGENHARIAS: ENGENHARIA DE MATERIAIS E METALURGICA